2000
DOI: 10.1029/2000jd900343
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to modeling tree rainfall interception

Abstract: Abstract. A three-dimensional physically based stochastic model was developed to describe canopy rainfall interception processes at desired spatial and temporal resolutions. Such model development is important to understand these processes because forest canopy interception may exceed 59% of annual precipitation in old growth trees. The model describes the interception process from a single leaf, to a branch segment, and then up to the individual tree level. It takes into account rainfall, meteorology, and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
2
12

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(135 citation statements)
references
References 41 publications
6
115
2
12
Order By: Relevance
“…Deterministic approaches to modelling evaporation by these processes have dominated the canopy interception literature (e.g. Rutter et al, 1971;Gash, 1979;Xiao et al, 2000a), and these models could serve as a way to use stochastic weather data to predict evaporation. The objectives of this research are only to estimate vegetation effects on precipitation in the statistical sense.…”
Section: Evaporationmentioning
confidence: 99%
“…Deterministic approaches to modelling evaporation by these processes have dominated the canopy interception literature (e.g. Rutter et al, 1971;Gash, 1979;Xiao et al, 2000a), and these models could serve as a way to use stochastic weather data to predict evaporation. The objectives of this research are only to estimate vegetation effects on precipitation in the statistical sense.…”
Section: Evaporationmentioning
confidence: 99%
“…Furthermore, urban trees store carbon [6], reduce rainwater runoff [7], and filter pollutants [8]. The moderation of microclimates and improvement of environmental conditions by urban trees has been analyzed by several studies [9][10][11][12][13], with results highlighting the importance of trees for cities and the city climate. Therefore, urban forests can also become a key component to the adaptation of cities to climate change [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although remote sensing may reduce the amount of field work needed, it cannot be excluded completely without a detrimental impact and high levels of uncertainty on the outcome of the task. It is important to accurately estimate LAI as Xiao et al (1998) found that modelling canopy interception was most sensitive to storage capacity and LAI as the storage capacity is directly related to the LAI. Similarly, Limousin et al (2008) found that a 25% reduction in storage capacity reduces interception loss by 8.6%…”
Section: Discussionmentioning
confidence: 99%